2016
DOI: 10.3892/ol.2016.4592
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of FISH for detecting upper tract urothelial carcinoma in voided urine specimens

Abstract: Abstract. The aim of the present study was to estimate the diagnostic value of fluorescence in situ hybridization (FISH) analysis of tumor cells in voided urine specimens for detecting upper tract urothelial carcinoma (UTUC). Cytology and FISH analyses were conducted on voided urine collected in the morning from 125 patients with suspected UTUC. During follow-up, ureteroscopy with biopsy and histopathology were used to confirm the presence of tumors. The average follow-up time was 23.8 months (range, 6-36 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…FISH was proven to be a sensitive method to detect bladder tumor as a noninvasive way and successfully used for the detection of molecular abnormalities in UTUCs . A recent study reported that the overall sensitivity and specificity of FISH in detecting UTUCs were 84.21% and 89.80%, respectively . In our study, the sensitivity of FISH in detecting HGUTUCs and LGUTUCs were 69.6% (32/46) and 60% (9/15), respectively.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…FISH was proven to be a sensitive method to detect bladder tumor as a noninvasive way and successfully used for the detection of molecular abnormalities in UTUCs . A recent study reported that the overall sensitivity and specificity of FISH in detecting UTUCs were 84.21% and 89.80%, respectively . In our study, the sensitivity of FISH in detecting HGUTUCs and LGUTUCs were 69.6% (32/46) and 60% (9/15), respectively.…”
Section: Discussionsupporting
confidence: 49%
“…1,10 A recent study reported that the overall sensitivity and specificity of FISH in detecting UTUCs were 84.21% and 89.80%, respectively. 30 In our study, the sensitivity of FISH in detecting HGUTUCs and LGUTUCs were 69.6% (32/46) and 60% (9/ 15), respectively. Although FISH and LBC had similar specificity (90.0% vs.94.4%), the sensitivity of FISH in detecting LGUTUCs was higher than that with LBC (33.3%).…”
Section: Discussionmentioning
confidence: 47%
“…In our larger cohort, we saw that patients with concurrent UW and VU specimens had a more severe diagnosis on UW cytology (21/32, 66%). More recently, Yu et al found that in a slightly larger cohort, the sensitivity of FISH in VU was significantly higher than that of VU cytology (84% vs.42%) for detecting UTUC, though the positive predictive value of FISH was slightly lower.…”
Section: Discussionmentioning
confidence: 96%
“…The sensitivity of CT scanning gradually increased with upstaging, which was incommensurable in FISH. However, FISH is noninvasive and can be used as a supplement for CT scan and urine exfoliative cytological examination [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%